THE GREEN SUPPLY CHAIN AND ITS IMPACT ON THE PERFORMANCE OF THE SUPPLY CHAIN ANALYTICAL STUDY IN THE UNION COMPANY FOR FOOD INDUSTRIES BABEL - Hamid Kazem Mutaab Al Shebawi; Fadila Hussain Aliwi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The current research aims to identify the green supply chain and its impact on the performance of the supply chain, an analytical study in the Union Food Industries Company Babel. and skills in their field of work, as their responses were recorded on a set of test items that were distributed to them in a questionnaire prepared by the researcher to identify the extent of interest and availability of the dimensions of the green supply chain in the researched company and the performance indicators of the supply chain in it. The results of the statistical analysis of the data showed the presence of positive indicators on providing the dimensions of the green supply chain in the Union Food Industries Company Babel and that these indicators are important and have a direct impact on improving the performance of the supply chain in the company. Therefore, the researcher recommends that companies should move towards protecting the environment through awareness of the pollution damage that they cause as a result of their operations and activities in the environment, and that the development of the industry must take place through increased attention to the dimensions of the green supply chain represented by design, purchasing, green manufacturing, rapid and effective treatment of waste and spreading environmental awareness to consumers And design a marketing mix to market green products according to market requirements.